Gender- and age-related benefit of renal replacement therapy on health-related quality of life - Kontodimopoulos, Nick; Pappa, Evelina; Niakas, Dimitris (Scandinavian journal of caring sciences, 2009)
Objectives:  The aim of this study was to compare the health‐related quality of life (HRQOL) of end‐stage renal disease patients on renal replacement therapy with that of subjects of the same gender and similar age from the general population, in an attempt to determine patient subgroup that benefits more from the treatment. Methods:  A cross‐sectional study involving haemodialysis, peritoneal dialysis and renal transplant patients (n = 874) was conducted with subjects providing socio‐demographic and disease‐related data, and completing the validated Greek Short Form‐36 (SF‐36) Health Survey. Patient‐specific z‐scores were calculated using mean SF‐36 scores and SD of age‐ and gender‐matched subgroups from the Greek norms. Results:  Males and younger patients generally reported better HRQOL. However, z‐scores in these groups generally showed a larger health deficit, i.e. an increased divergence from the HRQOL of their age‐ and gender‐matched counterparts of the general population, compared with the health deficit observed in female and younger patients. Conclusions:  Health‐related quality of life studies involving disease groups may sometimes be inconclusive if results are not compared with population norms, and particularly with subgroups matched for important demographic variables. Otherwise, as this study has shown, it is possible that important information may remain unrevealed.